Can an ecological-transactional systems model in occupational therapy contribute to a social prescribing programme?. Issue 2 (19th July 2021) - Johansson, Erika; Rapo, Emil; Nilsson, Ingeborg
Abstract : Purpose: The spread and level of loneliness is today considered a public health issue. Attempts to promote or reduce the level of loneliness have been made, one of which is social prescribing (SP), developed and extensively used. Complex interventions such as SP are advised to be connected to theory. Design/methodology/approach: For this purpose, the Person-Environment-Occupation-Participation model (PEOP) will be reviewed and used as an example, both as a way of organize occupational knowledge and as a model for practice. Findings: Occupational therapy underpinned by transactional system theory such as the PEOP model seems to give comprehensive and relevant support in the SP process. Particularly, this model can guide practitioners through crucial phases when assessing needs, matching interests and goals with relevant occupations, as well as understanding of important components embedded in the program. Originality/value: This opinion piece offers insights in why and how specific components connected to SP needs to be understood by theory and applied by personnel to facilitate a meaningful and sustainable occupational performance for the individuals.